2021
DOI: 10.1101/2021.02.15.431238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A farewell to EQ: A new brain size measure for comparative primate cognition

Abstract: Both absolute and relative brain size vary greatly among and within the major vertebrate lineages. Scientists have long debated how larger brains in primates and hominins translate into greater cognitive performance, and in particular how to control for the relationship between the non-cognitive functions of the brain and body size. One solution to this problem is to establish the slope of cognitive equivalence, that is the line connecting organisms with an identical bauplan but different body sizes. Here, we … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…For example, a recent analysis of mammalian brain size found the brain-to-body relationship to uncover more than just selection on brain size, indicating relative brain size measures, both residuals and EQ scores, are not accurately capturing brain size variation, and are not suitable for comparisons across species with different evolutionary histories [ 64 ]. Thus, van Schaik et al, [ 65 ] suggest the use of encephalisation quotients should be avoided in future studies, as EQs repeatedly fail to accurately predict brain size, and thus, varying levels of cognitive ability. For example, Deaner et al, [ 57 ] found absolute brain size measures, over statistically produced methods i.e., residuals, to be the best predictors of primate cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent analysis of mammalian brain size found the brain-to-body relationship to uncover more than just selection on brain size, indicating relative brain size measures, both residuals and EQ scores, are not accurately capturing brain size variation, and are not suitable for comparisons across species with different evolutionary histories [ 64 ]. Thus, van Schaik et al, [ 65 ] suggest the use of encephalisation quotients should be avoided in future studies, as EQs repeatedly fail to accurately predict brain size, and thus, varying levels of cognitive ability. For example, Deaner et al, [ 57 ] found absolute brain size measures, over statistically produced methods i.e., residuals, to be the best predictors of primate cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%
“…highly preferred food) in the feeding against preference task size and brain size are systematically larger in ectotherms than in endotherms (van Schaik et al, 2021;Tsuboi et al, 2018). Data on sexually dimorph primate species and on cleaner fish suggest that despite the different intraspecific slopes, cognitive performance is uncorrelated with body size (van Schaik et al, 2021;. Thus, the slopes seem to indicate equivalence in cognitive performance.…”
Section: Discussionmentioning
confidence: 93%
“…a: number of trials to complete reversal learning task; b: mean number of head bumps into Plexiglas separation in the detour task; c: % correct choices in the numerical competence task; d: mean number of flakes eaten before a prawn item (i.e. highly preferred food) in the feeding against preference task size and brain size are systematically larger in ectotherms than in endotherms (van Schaik et al, 2021;Tsuboi et al, 2018). Data on sexually dimorph primate species and on cleaner fish suggest that despite the different intraspecific slopes, cognitive performance is uncorrelated with body size (van Schaik et al, 2021;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Criticisms of using brain size measurements in comparative biology include that these measures do not actually capture variation in brain size across taxa well [69,70]. Some researchers contend that the number of cortical neurons, rather than brain size, is a better proxy for cognitive ability [71].…”
Section: Introductionmentioning
confidence: 99%